The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.0030-1299.2006.14223.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the species–time relationship across ecosystems and taxonomic groups

Abstract: 2006. A comparison of the species Á/time relationship across ecosystems and taxonomic groups. Á/ Oikos 112: 185 Á/195.The species Á/time relationship (STR) describes how the species richness of a community increases with the time span over which the community is observed. This pattern has numerous implications for both theory and conservation in much the same way as the species Á/area relationship (SAR). However, the STR has received much less attention and to date only a handful of papers have been published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
248
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(266 citation statements)
references
References 71 publications
13
248
3
2
Order By: Relevance
“…Turner & Tj0rve, 2005;Drakare et al, 2006;White et al, 2006) but despite this complication, two thirds of the variation in mosquito species richness for countries in this study is explained by area. Foley et al (2007) showed a similar species-area relationship using worldwide country species data.…”
Section: Discussionmentioning
confidence: 64%
“…Turner & Tj0rve, 2005;Drakare et al, 2006;White et al, 2006) but despite this complication, two thirds of the variation in mosquito species richness for countries in this study is explained by area. Foley et al (2007) showed a similar species-area relationship using worldwide country species data.…”
Section: Discussionmentioning
confidence: 64%
“…Species-time relationships (STR) were constructed using a sliding window approach (White et al, 2006;White and Gilchrist, 2007). Species richness was determined for every possible window of each time span: 12-year window, 11-year window, 10-year window etc.…”
Section: Methodsmentioning
confidence: 99%
“…This is because the power function suggests a constant percentage increase in species richness with each multiplicative increase in time scale, but the logarithmic function implies a constant absolute increase (see White et al, 2006 for detailed comparison of power and logarithmic function for STR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason is probably the general lack of comparable, high quality, long term studies of biodiversity, which are needed to study spatial patterns in temporal species turnover. To be clear, I'm not proposing anything new here, and aspects of β t, − → s has been addressed in earlier studies (as I'm sure the authors of McGill et al are well aware), for instance in Russell et al [3] and White et al [4], and the type of data presented in Dornelas et al [5] could also be used to this end. To conclude, I fully support the call in McGill et al [1] for an increased focus on aspects of β-diversity, and hope that β t, − → s will be recognized more clearly in studies of biodiversity change, even if we currently have few empirical studies that address this issue, especially at larger spatial scales.…”
mentioning
confidence: 99%